Giant intracranial aneurysm following radiation therapy: literature review with a novel case discussion - Paolucci, Aldo; Schisano, Luigi; Pluderi, Mauro; Grimoldi, Nadia; Caranci, Ferdinando; Angileri, Alessio; Arrichiello, Antonio; Costa, Antonella (Acta Biomedica Atenei Parmensis, 2020)
Background: The aim of this paper is to report the results of our review of the literature of published cases of intracranial aneurysms appearing after radiotherapy, and to present our case to add it to the current literature, in order to discuss the role of inflammation. Methods: We searched the PubMed database using combinations of the following MeSH terms: intracranial aneurysm, radiosurgery, radiotherapy, inflammatory changes in aneurysmal walls from 1967 to 2019. Results: 51 studies, for a total cohort of 60 patients, are described. The median latency between the radiation treatment and the diagnosis was 9,83 years, ranging from a minimum of 0,33 to a maximum of 33. The modality of rays’ administration was variable, and the dosage ranged from a minimum of 12 grays to a maximum of 177,2 grays. The anterior circulation appeared to be more frequently involved, and the most compromised vessel was the internal carotid artery. Radiation-induced vascular diseases have already been described in literature as well as RT-induced cellular and structural changes such as necrosis, macrophage or mononuclear cell infiltration, and several data support the role of inflammation in the development and remodelling of intracranial aneurysms, that, on one hand, favours them and, on the other, is necessary to their healing after endovascular treatment. Conclusions: Our team suggested a new insight in the management of these vascular lesions, which corresponds to a lower threshold when deciding whether or not to treat, and a longer and stricter follow-up.